Psychosocial Well-being in the Qur'an: A Contextual Analysis through the Lens of Social Theory - Mustakim, Ahmad; Rofhani, Rofhani; Sholihah, Fariha Akmaliatu (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2026)
This research article examines the foundations of the Qur'an as they relate to psychosocial well-being through a contextual hermeneutic approach that integrates contemporary social theory. By examining the concepts of sakinah, rahmah, ihsan, al-'adl, and ukhuah, this study aims to analyse how Qur'anic values can be reinterpreted to address modern psychosocial issues, particularly psychosocial well-being, arising from socio-economic inequality and cultural fragmentation. This research is a qualitative study using Berger & Luckmann's social construction theory and Giddens' structuralism theory as analytical lenses to explain how religious meanings are embedded in social practices and institutional arrangements. Methodologically, this qualitative study combines thematic content analysis of classical interpretations and contemporary literature (2015–2025) with theoretical triangulation. There are three findings: first, sakinah as a stabilizing psycho-spiritual mechanism. Second, rahmah–ihsan is a relational ethic that strengthens social cohesion. Third, al-'adl-ukhuah is a structural principle that facilitates collective prosperity. This study contributes a theoretical framework that operationalizes Qur'anic values within justice-oriented psychosocial interventions and social policies. The implications are relevant for mental health practitioners, policymakers, and academics researching religion-society relations. Penelitian ini mengkaji landasan-landasan Al-Qur’an terkait kesejahteraan psikososial melalui pendekatan hermeneutika kontekstual yang diintegrasikan dengan teori sosial kontemporer. Dengan menelaah konsep-konsep sakinah, rahmah, ihsan, al-‘adl, dan ukhuah, penelitian ini bertujuan untuk menganalisis bagaimana nilai-nilai Al-Qur’an dapat ditafsirkan ulang guna merespons isu-isu psikososial modern, khususnya terkait kesejahteraan psikologis, yang muncul akibat ketimpangan sosial-ekonomi dan fragmentasi budaya. Penelitian ini merupakan penelitian kualitatif yang menggunakan teori konstruksi sosial Berger & Luckmann dan teori strukturalisasi Giddens sebagai lensa analitis untuk menjelaskan bagaimana makna-makna keagamaan tertanam dalam praktik sosial dan pengaturan kelembagaan. Secara metodologis, studi kualitatif ini menggabungkan analisis isi tematik terhadap tafsir klasik, literatur kontemporer (2015–2025), dan triangulasi teoretis. Terdapat tiga temuan hasil: pertama, sakinah sebagai mekanisme psiko-spiritual yang menstabilkan. Kedua, rahmah–ihsan sebagai etika relasional yang memperkuat kohesi sosial. Ketiga, al-‘adl–ukhuah sebagai prinsip struktural yang memfasilitasi kemakmuran kolektif. Studi ini menyumbangkan kerangka teoretis yang mengoperasionalkan nilai-nilai Al-Qur’an dalam intervensi psikososial dan kebijakan sosial yang berorientasi pada keadilan. Implikasinya relevan bagi praktisi kesehatan mental, pembuat kebijakan, dan akademisi yang meneliti hubungan antara agama dan masyarakat.